COVID-19 and the Political Economy of Shared Adjustment - Ralf Boscheck (Intereconomics)
Abstract By April 2021, the COVID-19 crisis in Europe had reached a magnitude that, in the eyes of some observers, either deepened lingering divides and threatened the EU’s very existence, or, conversely, forced the Union to address the fundamental flaws of its euro area and provided an opportunity to reboot. From the outset, the EU had to confront fundamental challenges that require coordination; however, decentralised coordination is best as it improves the quality of policy, economic efficiency and civic virtues. While some argue for a debt union to provide the answer to the EU’s call for shared adjustment, a solution should rather be sought in economic reform, accountability and enforcement of constitutional commitments.